Outbreak of Equine Trypanosomiasis (Surra) with High Mortality in Horses in Chitwan, Nepal - Jibachha Sah; S. K. Prabhakar; S. K. Jyoti (The Indian Veterinary Journal, 2026)
An outbreak of equine trypanosomiasis (Surra) occurred in a horse riding facility in Chitwan, Nepal. Eight of fifteen horses died within 1–1.5 months before laboratory diagnosis. Affected horses showed fever, anemia, emaciation and icterus. Blood smear examination confirmed Trypanosoma spp. Early diagnosis and herd-level trypanocidal therapy are essential to prevent severe losses.